Owning Intellectual Leadership: Facing Down Academia’s Intellectual Neglect - Watermeyer , Richard; Sheridan, Mary (International Higher Education, 2025)
Geopolitical convulsions have exposed the scale of atrophy and impotency of academia’s intellectual contribution. While a contraction of intellectual leadership has been instinctively and perhaps idly blamed on higher education’s neoliberalization, academics’ apology neglects to address how their intellectual languor may also be operationalized into and obscured by a carousel of practices that academics have normalized, but should challenge.